Exploring bioactive compound origins: Profiling gene cluster signatures related to biosynthesis in microbiomes of Sof Umer Cave, Ethiopia - Abu Feyisa Meka; Gessesse Kebede Bekele; Musin Kelel Abas; Mesfin Tafesse Gemeda (PLoS ONE, 2025)
Sof Umer Cave is an unexplored extreme environment that hosts novel microbes and potential genetic resources. Microbiomes from caves have been genetically adapted to produce various bioactive metabolites, allowing them to survive and tolerate harsh conditions. However, the biosynthesis-related gene cluster signatures in the microbiomes of Sof Umer Cave have not been explored. Therefore, high-throughput shotgun sequencing was used to explore biosynthesis-related gene clusters (BGCs) in the microbiomes of Sof Umer Cave. The GeneAll DNA Soil Mini Kit was used to extract high-molecular-weight DNA from homogenized samples, and the purified DNA was sequenced using a NovaSeq PE150. According to the Micro-RN database, the most common microbial genera in Sof Umer Cave are Protobacteria, Actinobacteria, Verrucomicrobiota, and Cyanobacteria. The biosynthesis-related gene clusters were annotated and classified, and the BGCs were predicted using antiSMASH and NAPDOS1. A total of 460 putative regions of BGCs encoding a wide range of secondary metabolites were identified, including RiPP (47.82%), terpene (19.57%), NRPS (13.04%), hybrid (2.18%), and other newly annotated (10.87%) compounds. Additionally, the NAPDOS pipeline identified a calcium-dependent antibiotic gene cluster from Streptomyces coelicolor, an actinomycin gene cluster from Streptomyces chrysomallus, and a bleomycin gene cluster from Streptomyces verticillus. These findings highlight the untapped biosynthetic potential of the Sof Umer Cave microbiome, as well as its potential for the discovery of natural products.